2012
DOI: 10.1111/cch.12003
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurring development of early childhood communication and motor skills: results from a population‐based longitudinal study

Abstract: Our findings provide support for the hypothesis that these two difficulties are not symptoms of separate disorders, but might rather be different manifestations of a common underlying neurodevelopmental weakness. However, there also seem to be specific developmental pathways for each domain. Besides theoretical interest, more knowledge about the relationship between these early skills might shed light upon early intervention strategies and preventive efforts commonly used with children with problems in these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 32 publications
8
78
1
4
Order By: Relevance
“…Language skills was found to be associated with motor skills at both 1 ½, 3 and 5 years of age, and when controlling for the stability of development within each developmental domain motor skills at 1 ½ years of age still had a unique association to language skills at three years of age (17). From 3 to 5 years of age, controlling for the stability of each developmental domain the researchers found that language skills at three years of age uniquely predicted motor skills at five years of age, over and above what could be explained by earlier motor skills (18).…”
Section: Growth and Change In Language Development And Risk Factors Fmentioning
confidence: 86%
“…Language skills was found to be associated with motor skills at both 1 ½, 3 and 5 years of age, and when controlling for the stability of development within each developmental domain motor skills at 1 ½ years of age still had a unique association to language skills at three years of age (17). From 3 to 5 years of age, controlling for the stability of each developmental domain the researchers found that language skills at three years of age uniquely predicted motor skills at five years of age, over and above what could be explained by earlier motor skills (18).…”
Section: Growth and Change In Language Development And Risk Factors Fmentioning
confidence: 86%
“…This outcome is not surprising as children with SaLD often also have motor difficulties; in fact earlier research suggests that in some individuals, motor and communication difficulties may both be expressions of neurodevelopmental weakness with common origins (Wang, Lekhal, Aarø & Schjølberg, 2014). However, motor skills in children with SaLD are highly variable (Corriveau & Goswami, 2009), reflecting the complex interactions between speech, language and motor development (Goffman, Maassen, & Van Lieshout, 2010).…”
Section: Other Child Factorsmentioning
confidence: 98%
“…As discussed in more detail in Chapter 4, this rationale stemmed from a recent emphasis in the consideration of other developmental interactions within the child themselves which may influence the patterns of language development observed in early childhood. This previous work has focused on child-related influences including the impact of behaviour and also motor skills on language outcomes (Law, Rush, Parsons, & Schoon, 2013;McKean et al, 2015;Taylor et al, 2013;Wang, Lekhal, Aarø, & Schjølberg, 2014;Zubrick et al, 2007). The results from these previous studies suggest that more general developmental abilities may confer the risk for poor language outcomes.…”
Section: The Use Of Developmental Screening For Predicting Language Omentioning
confidence: 99%
“…Silva, McGee, & Williams, 1982), the few more recent studies in the area which have considered the predictive ability of early motor skills on long-term language outcomes in population-based cohorts present mixed findings. For example, Wang et al (2014) found in the Norwegian Mother and Child Cohort Study (n = 62,944) that early motor skills at 1.5 years predicted later communication skills at 3 years. On the other hand, another large-scale study (n = 13,016) found that gross and fine motor ability measured at 9 months, on the Denver Screening Test, was not a significant predictor of language performance at age 5 in the Millennium Cohort Study (Law et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation